High prevalence of incidental and symptomatic venous thromboembolic events in patients with advanced pancreatic cancer under palliative chemotherapy: a retrospective cohort study - Berger, Anne Katrin; Singh, Hans Martin; Sprick, Martin; Trumpp, Andreas; Jäger, Dirk; Springfeld, Christoph (Pancreatology, 2017)
Objectives: Pancreatic cancer patients are at high risk for venous thromboembolic events (VTEs), and chemotherapy is a known additional risk factor. In this context, there is a controversial discussion whether prophylactic anticoagulation should be offered to all outpatients receiving chemotherapy. Methods: In this retrospective study, we analyzed incidental and symptomatic VTEs in 150 pancreatic cancer patients receiving either gemcitabine-based chemotherapy or chemotherapy according to the FOLFIRINOX protocol. Results: VTEs were identified in 25% of patients, but were not associated with an adverse survival. There was no significant difference in VTE incidence between patients treated with gemcitabine-based chemotherapy or the more intensive FOLFIRINOX protocol. A commonly used risk score to predict VTEs in cancer patients did not predict the occurrence of VTEs in our patients. The occurrence of VTEs was not associated with one of the recently described pancreatic cancer subtypes. Conclusion: One quarter of pancreatic cancer patients treated with palliative chemotherapy develops symptomatic or incidental VTEs that cannot be predicted by type of chemotherapy, subtype of pancreatic cancer or a commonly used risk score. Further studies are necessary to identify patients at risk, and to better define which patients at risk should be treated with prophylactic anticoagulation.